1972
DOI: 10.1042/cs0430055
|View full text |Cite
|
Sign up to set email alerts
|

The Ventilatory Response to CO2 of Patients with Diffuse Pulmonary Infiltrations or Fibrosis

Abstract: S U M M A R Y1. We have used the rebreathing method to examine the respiratory response to CO, in five normal subjects and twelve patients with diffuse pulmonary infiltration or fibrosis. The response to CO, was measured in terms of both ventilation and mechanical work rate.2. The response to CO, was, on average, reduced in the patients compared with the normals but the patients had to perform more mechanical work to achieve a given level of ventilation.3. Six patients had an abnormally low resting mixed venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Patients with IPF are tachypneic; they develop more rapid shallow breaths as the disease progresses, and therefore the work of breathing is increased (123,124). This rapid respiratory rate is felt to be secondary to altered mechanical reflexes, because of the increased elastic load and/or vagal mechanisms, since no defined chemical basis for the hyperventilation has been identified (125)(126)(127)(128)(129)(130)(131)(132). Expiratory flow rates, forced expiratory volume in 1 s (FEV,), and forced vital capacity (FVC) are often decreased because of the reduction in lung volume, but the FEV,-to-FVC ratio is maintained or increased in IPF.…”
Section: Pulmonary Function Testingmentioning
confidence: 99%
“…Patients with IPF are tachypneic; they develop more rapid shallow breaths as the disease progresses, and therefore the work of breathing is increased (123,124). This rapid respiratory rate is felt to be secondary to altered mechanical reflexes, because of the increased elastic load and/or vagal mechanisms, since no defined chemical basis for the hyperventilation has been identified (125)(126)(127)(128)(129)(130)(131)(132). Expiratory flow rates, forced expiratory volume in 1 s (FEV,), and forced vital capacity (FVC) are often decreased because of the reduction in lung volume, but the FEV,-to-FVC ratio is maintained or increased in IPF.…”
Section: Pulmonary Function Testingmentioning
confidence: 99%
“…It has been suggested that the C 0 2 response of an individual is related to the ability to perform increased pulmonary work (5,10). The data obtained in this study of premature infants suggest that the infants who appear to be unresponsive to C 0 2 are either ( 1 ) performing respiratory work at the maximum rate possible or (2) truly lack reflexes for C 0 2 sensitivity.…”
Section: Discussionmentioning
confidence: 67%
“…A significant finding was the failure of some infants to increase either tidal volume or respiratory rate during COz rebreathing. It has been suggested that the C 0 2 response of an individual is related to the ability to perform increased pulmonary work (5,10). The data obtained in this study of premature infants suggest that the infants who appear to be unresponsive to C 0 2 are either ( 1 ) performing respiratory work at the maximum rate possible or (2) truly lack reflexes for C 0 2 sensitivity.…”
Section: Discussionmentioning
confidence: 67%